Effects of Anti-Inflammatory Treatment and Surgical Intervention on Endothelial Glycocalyx, Peripheral and Coronary Microcirculatory Function and Myocardial Deformation in Inflammatory Bowel Disease Patients: A Two-Arms Two-Stage Clinical Trial - Charilaos Triantafyllou; Maria Nikolaou; Ignatios Ikonomidis; Giorgos Bamias; Dimitrios Kouretas; Ioanna Andreadou; Maria Tsoumani; John Thymis; Ioannis Papaconstantinou (Diagnostics, 2021)
Sixty inflammatory bowel disease (IBD) patients (45 Crohn disease and 15 ulcerative colitis, 40 ± 13 years, 53% male) were examined at baseline and 4 months after intervention (surgical (35 patients) or anti-TNFa treatment (25 patients)). IBD severity, using Mayo score, Harvey–Bradshaw Index (HBI) and biomarkers, was correlated with cardiovascular markers. At baseline, the disease severity, the white blood cells (WBC) values and the reducing power (RP) were significantly correlated with the aortic pulse wave velocity (PWV) (r = 0.4, r = 0.44 and r = 0.48, p < 0.05) and the lateral mitral E’ velocity (r = 0.35, p < 0.05 and r = 0.3, p < 0.05). Four months after intervention, there was a reduction of WBC (1962.8/mm3 ± 0.425/mm3, p < 0.001), C-reactive protein (CRP) (8.1 mg/L ± 1.7 mg/L, p < 0.001), malondialdehyde (MDA) (0.81 nmol/mg ± 0.37, p < 0.05) and glycocalyx perfused boundary region (PBR 5-25) (0.24 μm ± 0.05 μm, p < 0.01). Moreover, the brachial flow mediated dilatation (FMD), the coronary flow reserve (CFR) and the left ventricle global longitudinal strain (LV GLS) were significantly improved for both groups (4.5% ± 0.9%, 0.55 ± 0.08, 1.4% ± 0.35%, p < 0.01), while a more significant improvement of PWV/GLS was noticed in the anti-TNFa group. IBD severity is associated with vascular endothelial, cardiac diastolic, and coronary microcirculatory dysfunction. The systemic inflammatory inhibition and the local surgical intervention lead to significant improvement in endothelial function, coronary microcirculation and myocardial deformation.